Panduan Kelayakan dan Pengukuran Kinerja Investasi PT Indo Inkubator Bisnis - Bachtiar, Arief Jenny; Supangkat, Hendrarto (Journal of Emerging Business Management and Entrepreneurship Studies, 2021)
The research in this thesis is motivated by the losses suffered by the venture capital company, PT Indo Inkubator Bisnis in acquiring a business partner. The purpose of this study is to formulate a guideline for the feasibility evaluation and performance measurement of the investment assets of PT Indo Incubator Bisnis. The results of the study concluded that there are six aspects that need to be evaluated before deciding to invest in a business partner. The six aspects are: legal aspects, operational aspects, market and competition aspects, key management aspects, financial aspects and valuation aspects. The results also concluded that there are four indicators that need to be routinely monitored for each business partner that has become the object of investment. The four indicators are: development of income value, development of profit value and margin level, development of dividend value, and development of share value of business units. The test results of the investment feasibility evaluation guide on the object of PT LMS conclude that this business unit is actually not a viable investment target. The results of the investment performance on the object of PT LMS also show that this investment asset does not have a good performance development.